2009
DOI: 10.1007/s11747-009-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of consumers’ online shopping cart abandonment

Abstract: Despite placing items in virtual shopping carts, online shoppers frequently abandon them -an issue that perplexes online retailers and has yet to be explained by scholars. Here, we identify key drivers to online cart abandonment and suggest cognitive and behavioral reasons for this non-buyer behavior. We show that the factors influencing consumer online search, consideration, and evaluation play a larger role in cart abandonment than factors at the purchase decision stage. In particular, many customers use onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(121 citation statements)
references
References 19 publications
8
113
0
Order By: Relevance
“…In fact, online shopping sites and some of the associated features such as online shopping carts are used by consumers simply as an 'entertainment or as a shopping research and organizational tool' [24]. Social media allows costeffective and personalized procedures for customers and can now change the intensity and meaning of messages in multiple ways [16,17].…”
Section: H2: the Positive Effect Of Interactional Justice On Customermentioning
confidence: 99%
“…In fact, online shopping sites and some of the associated features such as online shopping carts are used by consumers simply as an 'entertainment or as a shopping research and organizational tool' [24]. Social media allows costeffective and personalized procedures for customers and can now change the intensity and meaning of messages in multiple ways [16,17].…”
Section: H2: the Positive Effect Of Interactional Justice On Customermentioning
confidence: 99%
“…List of the determinants of consumers' online shopping cart abandonment was presented by Kukar-Kinney and Close [22]. They confirmed that categories of cart abandonment determinants should include entertainment value (using web page only for information purpose), concern about costs, waiting for better price, privacy and security concerns.…”
Section: Shopping Basket Analysismentioning
confidence: 88%
“…Analysis of the shopping cart can provide a valuable information about the needs and behavior of on-line and offline consumers. We can find many researches in the area of: what (and when) is being purchased [15] [19], shopping basket size and value analysis [16], effect of sales promotions on shopping basket [17][18], the cart filling time [20], the influence of smart shopping card on shopping behavior [21], or determinants of consumers' online shopping cart abandonment [22][23] [24].…”
Section: Shopping Basket Analysismentioning
confidence: 99%
“…Similarly, online retailers have found that a large proportion of customers go through the process of shopping, select the items that they like, and then abandon the shopping cart before completing the check out. 21 Strategies designed to encourage customers to complete the process by infl uencing their trying could produce positive results. Given that online marketers sell low value items in addition to high value items, similar approaches could also be used for low value items.…”
Section: Discussionmentioning
confidence: 99%